Sensory Detection by the Vomeronasal Organ Modulates Experience-Dependent Social Behaviors in Female Mice - Trouillet, Anne-Charlotte; Moussu, Chantal; Poissenot, Kevin; Keller, Matthieu; Birnbaumer, Lutz; Leinders-Zufall, Trese; Zufall, Frank; Chamero, Pablo (Frontiers in Cellular Neuroscience, 2021)
In mice, social behaviors are largely controlled by the olfactory system. Pheromone detection induces naïve virgin females to retrieve isolated pups to the nest and to be sexually receptive to males, but social experience increases the performance of both types of innate behaviors. Whether animals are intrinsically sensitive to the smell of conspecifics, or the detection of olfactory cues modulates experience for the display of social responses is currently unclear. Here, we employed mice with an olfactory-specific deletion of Gαi2, which partially eliminates sensory function in the vomeronasal organ (VNO), to show that social behavior in female mice results from interactions between intrinsic mechanisms in the vomeronasal system and experience-dependent plasticity. In pup- and sexually-naïve females, Gαi2 deletion elicited a reduction in pup retrieval behavior, but not in sexual receptivity. By contrast, experienced animals showed normal maternal behavior, but the experience-dependent increase in sexual receptivity was incomplete. Further, lower receptivity was accompanied by reduced neuronal activity in the anterior accessory olfactory bulb and the rostral periventricular area of the third ventricle. Therefore, neural mechanisms utilize intrinsic sensitivity in the mouse vomeronasal system and enable plasticity to display consistent social behavior.